El problema de la administración de justicia “lega” y “experta” en Chile siglo XIX. El valor heurístico de los expedientes judiciales - Víctor Brangier (Centre de Recherches sur les Mondes Américains, 2012)
The paper analyzes two cases presented in a session of this workshop, from the perspective of the relationship between lay and expert justice in Chile in the mid-nineteenth century. After contrasting the informative value of these sources with official output documents such as legislation and ministerial archives, the study aims to outline the specific utility of court cases in the examination of the complexity of local judicial practice. Ultimately, it is argued that such judicial sources provide the ability to discern, not only the tensions between lay and legal justice, the later was imposing gradually throughout the territory, but also gives clues about the transactions, adjustments and mutual loans between both spheres.